2013
DOI: 10.1111/jgs.12210
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic Management of Dementia Across Settings of Care

Abstract: Objectives To describe population-based use of cognitive-enhancing and psychopharmacological medications across care settings among Medicare beneficiaries with dementia. Design One-year (2008) cross-sectional study Setting Medicare administrative claims froma 5% random sample Participants 52,754 Medicare beneficiaries with dementia aged ≥65 years with continuous Medicare Parts A, B, and D coverage and alive throughout 2008. To ascertain dementia, ≥1 medical claim with a dementia ICD-9-CM code was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
5
24
4
Order By: Relevance
“…We did not find changes in antidepressant use during the years 2005-2011 except decreasing use of tricyclics and SSRIs and corresponding increase in use of "other antidepressants" like mirtazapine. Other previous studies (Guthrie et al, 2010;Rhee et al, 2011;Rattinger et al, 2013) have reported antidepressant use in samples including persons with differing times since diagnoses and thus, are not directly comparable to our study including newly diagnosed persons with AD.…”
Section: Discussioncontrasting
confidence: 68%
“…We did not find changes in antidepressant use during the years 2005-2011 except decreasing use of tricyclics and SSRIs and corresponding increase in use of "other antidepressants" like mirtazapine. Other previous studies (Guthrie et al, 2010;Rhee et al, 2011;Rattinger et al, 2013) have reported antidepressant use in samples including persons with differing times since diagnoses and thus, are not directly comparable to our study including newly diagnosed persons with AD.…”
Section: Discussioncontrasting
confidence: 68%
“…The most frequently prescribed medications are cholinesterase inhibitors (e.g., galantamine, donep ezil and rivastigmine) and NMDA antagonists (e.g., memantine), reported in 50%-90% of cases. [27][28][29] Our estimate for the proportion of patients prescribed these medications by their primary care provider was lower than that reported elsewhere and may reflect legitimate uncertainty in Canada about their effectiveness. 30,31 It may also reflect incomplete recording of prescribing by specialists in primary care EMRs.…”
Section: Discussioncontrasting
confidence: 49%
“…We used BMI values recorded in the EMR; if no value was present, we calculated it using the most recent height and weight values. We classified the BMI values as underweight (< 18), normal (18)(19)(20)(21)(22)(23)(24), overweight (25)(26)(27)(28)(29) and obese (≥ 30). We determined residence in rural or urban areas using the second digit of the patient's postal code (0 indicates rural; other values indicate urban).…”
Section: Variables Of Interestmentioning
confidence: 99%
“…We drew from measure definitions in the literature and conducted claims-based sensitivity analyses to optimize the measure construct when possible. [4][5][6][7][8][9][10] ] For example, we studied the characteristics and follow-up events for those we deemed "low risk" for the cardiac screening measure. All measures not drawn from the literature were developed by a clinician; each was then reviewed by a second clinician.…”
Section: Choosing Wisely Measurementmentioning
confidence: 99%